Strongly and Semi Strongly E_h-b-Vex Functions: Applications to Optimization Problems - Majeed, Saba Nasser (Iraqi Journal of Science, 2019)
In this paper, we propose new types of non-convex functions called strongly --vex functions and semi strongly --vex functions. We study some properties of these proposed functions. As an application of these functions in optimization problems, we discuss some optimality properties of the generalized nonlinear optimization problem for which we use, as an objective function, strongly --vex function and semi strongly --vex function.